A modular approach to carbene-stabilized diphosphorus species. Issue 45 (8th November 2017) - Doddi, Adinarayana; Bockfeld, Dirk; Zaretzke, Marc-Kevin; Kleeberg, Christian; Bannenberg, Thomas; Tamm, Matthias
Abstract : A modular approach has been developed for the synthesis of a series of neutral, cationic and dicationic heteroleptic dicarbene–diphosphorus species. Abstract : Heteroleptic N-heterocyclic dicarbene–diphosphorus species were prepared by reaction of the carbene–phosphinidene adduct (IPr)PSiMe3 (1, IPr = 1, 3-bis(2, 6-diisopropylphenyl)imidazolin-2-ylidene) with the carbene–phosphorus trichloride adduct (IMes)PCl3 (2, IMes = 1, 3-bis(2, 4, 6-trimethylphenyl)imidazolin-2-ylidene), which furnished the dichloride [(IPr)PPCl(IMes)]Cl (3 ). Reduction of3 with potassium graphite (KC8 ) afforded [(IPr)PP(IMes)] (4 ). The corresponding radical cation [(IPr)PP(IMes)]˙ + (5 ˙ + ) is isolated as [5 ]PF6 by reaction of4 with ferrocenium hexafluorophosphate, whereas complexes containing the corresponding dication [(IPr)PP(IMes)] 2+ (6 2+ ) can be isolated as the gallate and borate salts [6 ](GaCl4 )2 and [6 ](BAr F )2 by chloride abstraction from3 with GaCl3 or sodium tetrakis[bis(3, 5-trifluoromethyl)phenyl]borate (NaBAr F ), respectively. The asymmetric set of N-heterocyclic carbene ligands allows to establish 1 J PP coupling constants of 249 Hz for4 and 543 Hz for [6 ](GaCl4 )2 . Based on X-ray diffraction analyses, the molecular structures of4, 5 ˙ + and6 2+ reveal a consecutive shortening of the P–P bond lengths, in agreement with the presence of a phosphorus–phosphorus single bond in4 and a double bond in6 2+, which is best described as a dicationic diphosphene according to density functional theory (DFT) calculations.